KONSTRUKSI PEMBERITAAN EFEK SAMPING VAKSIN ASTRAZENECA PADA MEDIA ONLINE KOMPAS.COM DAN DETIK.COM - Marbun, Angel Mei; Sholihul Abidin (LPPM Universitas Putera Batam, 2022)
The spread of the corona virus is so fast almost to all corners of the world, including to Indonesia. Various kinds of policies carried out by the Indonesian government to ward off this virus, one of which is the vaccination policy. However, there are still many people who doubt this Covid 19 vaccine, especially the AstraZeneca vaccine. News about the side effects of the AstraZeneca vaccine was also published in online media Kompas.com and Detik.com. To see how the construction of side effect reporting in the two online media requires framing analysis to find out how the perspective used by the media in selecting issues and writing news. The purpose of this study was to find out how the two online media Kompas.com and Detik.com build a news story on the case of reporting on the side effects of the Astrazeneca vaccine. This type of research is descriptive qualitative research, using the framing analysis method of Robert N.Entman. The results of this study show that Kompas.com and Detik.com have similarities that the side effects of the AstraZeneca vaccine are mild. Keywords: Astrazeneca Vaccine, Media Online, Robert N. Entman Framing Analysis.